1998
DOI: 10.1111/j.1365-2664.1998.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental parameters on the distribution of bullhead Cottus gobio with particular consideration of the effects of obstructions

Abstract: 1.The bullhead Cottus gobio is a small-sized fish that occurs in stony streams and lakes in Switzerland. Its numbers have declined and its distribution has become narrower over the last 30 years, most probably due to chemical pollution and/or structural habitat deterioration, and at present it is classified as a potentially endangered species. 2. This study evaluated whether chemical parameters and/or structural habitat heterogeneity have an effect on the occurrence and density of bullhead in a river system, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 16 publications
7
71
1
1
Order By: Relevance
“…In contrast, one population showed substantially higher densities of 75 individuals·m -2 (Mann, 1971). Jansen et al (2000) and Utzinger et al (1998) found densities in the range of 1.8-14.7 individuals·m -2 . Appreciable differences in bullhead abundance from site to site were also found in the Garonne stream system (Legalle et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In contrast, one population showed substantially higher densities of 75 individuals·m -2 (Mann, 1971). Jansen et al (2000) and Utzinger et al (1998) found densities in the range of 1.8-14.7 individuals·m -2 . Appreciable differences in bullhead abundance from site to site were also found in the Garonne stream system (Legalle et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, Perrow et al (1997) and Gosselin et al (2010) observed a positive correlation between bullheads and greater depths and slow velocity. In fact, there is an ontogenetic shift and seasonal changes in the preferences of sculpins for water depth, velocity and size of the substrata (Carter et al, 2004;Van Liefferinge et al, 2005) and the bullhead may be more flexible in its habitat requirements than generally assumed (Utzinger et al, 1998;Jansen et al, 2000). Most studies have found that bullheads avoid muddy bottoms and homogeneous areas and wider sections of the river (Legalle et al, 2005;Gosselin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations